Baw Gaow Phase IV/Cham Luang Phase II Tribal Detoxification and Rehabilitation Project : final report (The Project, 1994)
Reviews the results of previous phases and makes recommendations regarding future phases of narcotics detoxification and rehabilitation projects at Baw Goaw Rehabilitation Center and Cham Luang Detox/Rehab Center, both located in Karen-Hmong tribal area northwest of Chiangmai, Thailand.